Analysis of the Cochrane Review: Pharmacotherapy for Hyperuricemia in Hypertensive Patients. Cochrane Database Syst Rev. 2017;4:CD008652.] - Bigotte Vieira, M (2017)
Arterial hypertension is a public health problem that affects approximately 25% of the world's adult population. The association between hypertension and hyperuricemia has been shown on epidemiological and experimental studies. However, it is unclear whether lowering serum uric acid might lower blood pressure. This Cochrane systematic review - a revised edition of a previously published one - intended as primary objective to evaluate the effect of hypouricemic drugs in patients with primary hypertension or prehypertension. The secondary objectives were to evaluate the efficacy and safety of hypouricemic drugs. A systematic search until February 2016 on controlled, randomized or quasi-randomized trials comparing the effect of hypouricemic drug versus placebo in hypertensive or prehypertensive patients was performed on the following databases: The Cochrane Hypertension Specialised Register, the Cochrane Central Register of Controlled Trials (CENTRAL), Medline, Embase, The World Health Organization International Clinical Trials Registry Platform, e ClinicalTrials.gov. LILACS database up to March 2016 was also searched and the authors of relevant studies were contacted. There were 349 identified papers, 21 were preselected and three randomized clinical trials (211 patients) were included in the qualitative analysis and in the meta-analysis. Two of the trials were conducted exclusively on adolescents. The authors conclude that hypouricemic drugs are not effective in lowering blood pressure in patients with hyperuricemia and primary prehypertension or hypertension. However, this strategy might be more effective in the specific population of adolescents with prehypertension or mild primary hypertension recently diagnosed. Hypouricemic drugs effectively reduce serum uric acid level and withdrawals of therapy due to adverse effects were not superior in the treated group, comparing to placebo; however, one patient withdrew due to a severe cutaneous reaction.